Biotin-mediated epigenetic modifications: Potential defense against the carcinogenicity of benzo[a]pyrene. (22nd January 2016) - Xia, Bo; Pang, Li; Zhuang, Zhi-xiong; Liu, Jian-jun
Highlights: Provides an overview of the epigenetic events caused by benzo[a]pyrene. Provides an overview of the epigenetic events associated with biotin. Discussed the possibility of nutritional treatment against tumorigenesis. Biotin supplement may potentially reduce the risk of cancer induced by B[a]P. Abstract: Environmental pollution and an unhealthy lifestyle result in direct exposure to dangerous chemicals that can modify endogenous pathways and induce malignant transformation of human cells. Although the molecular mechanisms of tumorigenesis are still not well understood, epigenetic alteration may be associated with exogenous chemical-induced carcinogenicity. Given the association between nutrition and cancer, nutrient supplementation may reduce aberrant epigenetic modifications induced by chemicals, thus decreasing carcinogenesis. This paper provides an overview of the epigenetic events caused by benzo[a]pyrene, a procarcinogenic and environmental pollutant, and biotin, an essential water-soluble vitamin, and investigates potential connections between them. This paper also discusses the potential inhibitory effect of biotin-related epigenetic modifications on the carcinogenicity of benzo[a]pyrene. The effect of nutritional supplementation on tumorigenesis involving epigenetic modifications is also discussed.